The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1093/icvts/ivw196
|View full text |Cite
|
Sign up to set email alerts
|

Bileaflet mechanical valve replacement: an assessment of outcomes with 30 years of follow-up

Abstract: Low late mortality and a low incidence of valve-related events can be achieved for at least 30 years using mechanical bileaflet valve replacement. Persistent atrial fibrillation is a significant risk factor for morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
0
13
1
Order By: Relevance
“…4 During 34-year follow-up, the mortality rate was 0.59%/year for cardiac death and 0.69%/year for valverelated death. 4 At multivariable analysis, the Authors found that male sex was associated with an increased risk of death (HR 1.25, 95%CI 1.11-1.42, P = .0003), but the analysis was not apparently adjusted for comorbidities and antithrombotic treatments, including anticoagulation quality. 4 We found low anticoagulation quality, high INR range, ageing and comorbidities as the most important factors associated with mortality, both in the aortic and mitral MPHV group.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…4 During 34-year follow-up, the mortality rate was 0.59%/year for cardiac death and 0.69%/year for valverelated death. 4 At multivariable analysis, the Authors found that male sex was associated with an increased risk of death (HR 1.25, 95%CI 1.11-1.42, P = .0003), but the analysis was not apparently adjusted for comorbidities and antithrombotic treatments, including anticoagulation quality. 4 We found low anticoagulation quality, high INR range, ageing and comorbidities as the most important factors associated with mortality, both in the aortic and mitral MPHV group.…”
Section: Discussionmentioning
confidence: 98%
“…4 At multivariable analysis, the Authors found that male sex was associated with an increased risk of death (HR 1.25, 95%CI 1.11-1.42, P = .0003), but the analysis was not apparently adjusted for comorbidities and antithrombotic treatments, including anticoagulation quality. 4 We found low anticoagulation quality, high INR range, ageing and comorbidities as the most important factors associated with mortality, both in the aortic and mitral MPHV group. Our finding that low TiTR < 60% is associated with an increased mortality risk supports and extends previous evidence that high variability of INR was associated with poor survival in patients undergoing single valve replacement (HR 1.8 per 20% increase).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The open-label, single-center randomized controlled noninferiority trial 19 In a 30-year retrospective cohort analysis of 950 AVR at a single center in Japan, 88.6%, 89.8%, and 94.4% of AVR patients were free from valve-related mortality, thromboembolic events, and bleeding events, respectively, after 30 years when anticoagulated to a target INR of 1.6 to 2.5. 20 Atrial fibrillation independently predicted increased risk of TE and age older than 70 years, and previous operation independently predicted anticoagulation-related hemorrhage. Although this study helps to justify lower INR goals, it is important to note that lower target INR goals have been proposed in Japan due to a higher risk of warfarin-related intracranial hemorrhage and these same goals may not be appropriate in Caucasian populations.…”
Section: St Jude Bileaflet Valvementioning
confidence: 96%
“…Traditional open-chest surgery has the advantage of good exposure of the surgical field, which can markedly shorten cardiac arrest and cardiopulmonary bypass (CPB) times, but also has disadvantages of large surgical wounds, more bleeding, severe pain, and slow postoperative recovery [7,8] . Total thoracoscopic and thoracoscopic-assisted cardiac surgery have emerged in recent years [9-11] .…”
Section: Introductionmentioning
confidence: 99%